Hesitancy among Iranian nursing students regarding future career trajectory: a qualitative analysis - Farnoosh Shafiei; Mostafa Amini-Rarani; Koen Ponnet; Maryam Moeeni (BMC, 2024)
Abstract Background The shortage of skilled nurses is a major concern for health systems worldwide. This may be partly due to the hesitancy of some nurses to enter or remain in the nursing career. This shortage consequently reduces the quality of standard patient care, increases patients' length of stay in a hospital, increases medical costs, and results in patients' dissatisfaction. This study aimed to explore hesitancy among senior undergraduate nursing students to pursue a career in nursing. Methods This qualitative study adopted a thematic analysis approach. The population comprised senior undergraduate nursing students at Isfahan University of Medical Sciences, Iran, who indicated that they were hesitant to pursue a career in nursing. The study sampling was performed from May 2021 till February 2022 and continued until data saturation. Twenty-four interviews were conducted with the selected students. The attributes related to hesitancy among senior undergraduate nursing students to pursue a career in nursing were extracted as themes and sub-themes. Results Four themes were identified: academic idiosyncrasies, individual characteristics, poor nursing market regulations (sub-themes: nursing as a tough and intense career, and unfavorable employment contracts), and the peculiarities of the workplace (sub-themes: conflict within work environment, and barriers to professional nursing practice). Conclusions The findings of this study showed that senior undergraduate nursing students weigh their future career options from various academic, personal, professional, and work environment dimensions. The findings provide new insights for decision makers to design and implement innovative strategies to promote retention in nursing careers. We recommend to provide academic counseling for all students and applicants of nursing before they enter the nursing education. Furthermore, we suggest to improve study and work environments, and to implement incentive programs to enhance enthusiasm of nursing students for pursuing a nursing career.